Content Analysis in the English Textbook “Bahasa Inggris” for the eleventh grade Students of Senior High School - 12, Yuvia (Institut Agama ISlam Negeri Palangka Raya, 2022)
The purpose of this study was to analyze and determine the suitability and suitability of the contents of the teaching materials in the form of